THE DISTRIBUTION OF IODINE IN THE EARTH'S CRUST - Muramatsu Y.; Wedepohl K.H. (My University, 1998)
Analytical data by ICP-MS measurements after pyrohydrolysis on a reasonably large series of samples representing about 300 rocks of major units and subunits of the earth's crust, and a few organic materials, are provided for a genetic discussion. Biogenic accumulation and volatilization of iodine from metamorphosed sediments and magmatic rocks has caused extreme gradients of concentrations towards the top of the oceanic and continental crust. Transporting agents for recycling into surface water were hydrothermal fluids and partial volatilization from surface waters which occurred as methyl iodide. Because of the low iodine concentrations in magmatic and metamorphic rocks such samples exposed at the earth's surface not far from the seashore could have undergone contamination by iodine which escaped from the oceans. The high average concentrations of 30 ppm I in deep-sea carbonates and of 2.5 ppm I in continental limestones were accumulated by planktonic and shallow sea organisms, respectively. Deep-sea clays (3.9 ppm I) and continental shales (1.8 ppm I) contain the residual iodine after dissolution and oxidation of a major fraction of carbonates and organic carbon, respectively. Shales vary more in iodine than deep-sea clays because of greater variations in the environments of deposition and diagenesis. The I/C weight ratio increases from 10-3 to 2 # 10-1 from reduced to oxygenated recent nearshore sediments. Iodine is more stable than carbon during diagenesis of biogenic sediments. Greywackes and sandstones contain on average 150 and 120 ppb I, respectively. Metasedimentary gneisses, mica schists and granulites have as little as 12 to 25 ppb I and have lost from 75 to > 95% of their iodine at metamorphic temperatures. Granites, granodiorites, tonalites and basalts are even lower in iodine and contain 4 to 9 ppb I almost independent of the species of magmatic rock. The continental crust, the oceanic crust (including seawater) and bulk Earth's crust contain 119 ppb, 777 ppb and # 300 ppb I, respectively. Nearly 70% of I is calculated to exist in ocean sediments. The Cl/I weight ratios of the continental, oceanic and bulk Earth's crust are 3800, 4500 and 4300, respectively, to be compared with 1210 and 403 in the Orgueil and Ivuna Cl chondrites.
Keywords: ICP-MS AFTER PYROHYDROLYSIS; BIOLOGIC ACCUMULATION IN SEDIMENTS; VERY LOW I IN METAMORPHIC AND MAGMATIC ROCKS; HYDROTHERMAL TRANSPORT